'Extra oomph:' addressing housing disparities through Medical Legal Partnership interventions. Issue 7 (2nd October 2016) - Hernández, Diana
Abstract: Low-income households face common and chronic housing problems that have known health risks and legal remedies. The Medical Legal Partnership (MLP) program presents a unique opportunity to address housing problems and improve patient health through legal assistance offered in clinical settings. Drawn from in-depth interviews with 72 patients, this study investigated the outcomes of MLP interventions and compares results to similarly disadvantaged participants with no access to MLP services. Results indicate that participants in the MLP group were more likely to achieve adequate, affordable, and stable housing than those in the comparison group. Study findings suggest that providing access to legal services in the healthcare setting can effectively address widespread health disparities rooted in problematic housing. Implications for policy and scalability are discussed with the conclusion that MLPs can shift professionals' consciousness as they work to improve housing and health trajectories for indigent groups using legal approaches.